Berthold Lubetkin's Highpoint II and the Jewish contribution to modern English architecture - Lewittes, Deborah, author.
1 online resource (ix, 97 pages)
Keywords: "In 1935, the Russian-born Jewish architect Berthold Lubetkin and his firm Tecton designed Highpoint, a block of flats in London which Le Corbusier called revolutionary. Three years later, Lubetkin completed a companion design. Yet Highpoint II felt very different and the sense that the ideals of modernism had been abandoned seemed hard to dispute. Had modern architecture failed to take root in England? This book challenges the belief that English architecture was on hiatus during the 1930s. Using Highpoint II as a springboard, Deborah Lewittes takes us on a journey through the defining moments of modern English architecture the high points of the period surrounding Highpoint II. Drawing on Lubetkins work and his writings, the book argues that he advanced influential, lasting theories which were rooted in his design for Highpoint II. Lubetkins work is explored within the context of wider Jewish emigration to London during the interwar years as well as the anti-semitism that pervaded Britain during the 1930s. As Lewittes demonstrates, this decade was anything but quiet. Providing a new perspective on twentieth century English architecture, this book is of interest to students and scholars in architectural history, urban studies, Jewish studies, and related fields."--Provided by publisher.